Estudantes de ensino médio e COVID-19: apropriações acerca do conceito de vírus sob a perspectiva vigotskiana - Cunha, Alexia Liara (2023)
This research addresses the formation of concepts from the Vygotskian perspective, through a didactic sequence, whose central theme was the COVID-19 pandemic. The sequence was elaborated and applied in the elective discipline with high school students from a state public school in São Miguel Arcanjo/SP. This research proposes to discuss the following question: What contributions can a didactic sequence, using the pandemic period as a context, offer to the development of scientific concepts/knowledge? The research objectives were 1) producing and discussing the application of a didactic sequence with the most general theme of the pandemic context; 2) discussing the appropriation carried out by the students from the application of this sequence and, 3) identifying the conceptual elaboration, especially the concept of virus, using exercises and activities carried out by the students. The bibliographic review presented in this dissertation indicated that concept formation is the point in almost all the works consulted. This shows us this is one of the important aspects of the Vygotskian approach and that several authors are committed to studying it, especially when dealing with activities developed in the classroom, as is the case of this research. Studies of this source are even more relevant in the educational scenario of secondary education reform. Three questionnaires were applied throughout the execution of the didactic sequence: the lifting of previous ideas (LPI) that started the didactic sequence; the intermediate questionnaire, elaborated with questions similar to those of the LPI and applied right after the end of the sequence; and the final questionnaire, designed to understand if generalization processes occurred months after the application of the didactic sequence. As contributions promoted by the didactic sequence, we mention the research of a relevant and concrete theme, experienced not only by the students involved, but by the world population; filling in gaps on the subject and research on the development of concepts related to the COVID-19 pandemic. When comparing the three questionnaires, it is possible to assure that, despite a few mistakes, the students performed well in the course of concept formation.